Penerapan Metode EUCS dan SMARTPLS Terhadap Pengukuran Tingkat Kepuasan Pengguna Aplikasi Zalora - Budiman, Muhammad Arif; Sanjaya, M. Rudi; Endang Lestari Ruskan; Indah Dwi Rosa (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Zalora is an E-Commerce aplplication founded on 2012 in Singapore and now operates in various countries, including Indonesia. Although widely known, this application still has a number of complaints from users such as product incompatibility, delays in process updates, and less than optimal application performance. This study aims to evaluate user satisfaction with the Zalora application using the EUCS method, which includes five variables, namely Content, Accuracy, Format, Ease of Use, and Timeliness. This study provides benefits for application, with the subjects being student college members of the Faculty of Computer Science at Sriwijaya University. This study employs a quantitative approach, utilizing data collection through questionnaires and analysis with SmartPLS software. As a result, the five EUCS method variables positively impact user satisfaction, particularly the Content, Accuracy, Ease of Use and Timeliness variables.